2023
DOI: 10.3390/ijms24109006
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular-Vesicle-Based Therapeutics in Neuro-Ophthalmic Disorders

Abstract: Extracellular vesicles (EVs) have been recognized as promising candidates for developing novel therapeutics for a wide range of pathologies, including ocular disorders, due to their ability to deliver a diverse array of bioactive molecules, including proteins, lipids, and nucleic acids, to recipient cells. Recent studies have shown that EVs derived from various cell types, including mesenchymal stromal cells (MSCs), retinal pigment epithelium cells, and endothelial cells, have therapeutic potential in ocular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 145 publications
(159 reference statements)
0
9
0
Order By: Relevance
“…Preliminary screening of drugs in such an ex vivo retina system avoids all issues and uncertainties related to systemic (i.e., vascular) or intraocular transport and delivery. It is, thus, agnostic in terms of the nature of the formulation being tested, irrespective of its molecular weight (including recombinant proteins [4]) and hydrophobicity (e.g., 9-cis-retinal; Figure 4), spanning from simple solutions to suspensions, emulsions and nano-carriers such as liposomes [4] and exosomes [26]. Lastly, concurrent recordings from four retinas double the experimental throughput.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary screening of drugs in such an ex vivo retina system avoids all issues and uncertainties related to systemic (i.e., vascular) or intraocular transport and delivery. It is, thus, agnostic in terms of the nature of the formulation being tested, irrespective of its molecular weight (including recombinant proteins [4]) and hydrophobicity (e.g., 9-cis-retinal; Figure 4), spanning from simple solutions to suspensions, emulsions and nano-carriers such as liposomes [4] and exosomes [26]. Lastly, concurrent recordings from four retinas double the experimental throughput.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are a diverse group of lipid bilayer-encased particles that are characterized by their heterogeneity in size (ranging from 30 to 1000 nm), origin (secreted by nearly all cell types), and composition [ 1 , 2 ]. These endogenously produced particles have the inherent capacity to convey a wide range of bioactive molecules comprising proteins, nucleic acids, and lipids.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple classifications of EVs based on their origin, size, and functionality. Three major sub-types of EVs are apoptotic bodies (1000–5000 nm), microvesicles (MVs) or ectosomes (100–1500 nm), and exosomes (30–100 nm) [ 1 , 8 , 9 , 10 ]. EVs are found in all body fluids, including plasma, urine, breast milk, saliva, and tears [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 The performance of cellderived EVs in Ophthalmology has been studied on multiple diseases, and the focus has mostly been on their regeneration function for neuro or specific component cells. 6 Studies on EVs derived from Candida albicans, Dermatophyte Trichophyton, Cryptococcus, and others have revealed that the immunogenic components within these cargo materials impact host immune function. 7−13 Due to their cell-free nature and the presence of multiple pathogen-associated molecular patterns (PAMPs), EVs possess the ability to induce robust and sustained immune responses.…”
mentioning
confidence: 99%
“…The cargo carried by EVs exhibits specific heterogeneity based on their origin species, environmental factors, and growth stages . The performance of cell-derived EVs in Ophthalmology has been studied on multiple diseases, and the focus has mostly been on their regeneration function for neuro or specific component cells . Studies on EVs derived from Candida albicans, Dermatophyte Trichophyton, Cryptococcus, and others have revealed that the immunogenic components within these cargo materials impact host immune function. Due to their cell-free nature and the presence of multiple pathogen-associated molecular patterns (PAMPs), EVs possess the ability to induce robust and sustained immune responses. Pre-emptive application of fungal EVs to the host has shown to mitigate the lethality of fungal infections and reduce tissue destruction caused by the immune response of the host. , …”
mentioning
confidence: 99%